Perlindungan Data Pribadi Konsumen Lazada Dalam Transaksi E-Commerce - Simarmata, Rikson; Akyuwen, Rory Jeff; Pesulima, Theresia Louize (PATTIMURA Law Study Review, 2024)
ABSTRACT: The problem in this thesis is about the negligent actions of business actors in protecting consumers' personal data in Lazada E-Commerce Transactions. Based on Law No. 11 of 2008 concerning ITE Article 26 Paragraph 1, it can be seen that the use of any information via electronic media that concerns a person's personal data must have the consent of the person concerned. This research aims to ensure that every business actor who carries out e-commerce transactions is careful in disseminating consumer personal data, and every business actor is required to first obtain permission from the consumer concerned before disseminating personal data. The method used in this research is normative juridical with a statutory approach and a conceptual approach. The legal materials used are primary and secondary legal materials which are analyzed qualitatively to answer the problems studied. Based on this research, Lazada consumer personal data protection in e-commerce transactions consists of preventive protection and repressive legal protection. Preventive protection carried out by the government is monitoring and checking the suitability of electronic systems and internal arrangements for electronic system operators to prevent losses from occurring to consumers who carry out e-commerce transactions. Repressive Protection is in the form of compensation for losses caused by leakage of consumers' personal data by business actors. Efforts to resolve disputes consist of two channels, namely litigation (court) to sue for compensation and non-litigation channels with alternative dispute resolution in the form of negotiation, mediation, conciliation, expert opinions and arbitration.